RAPTOR up-regulation contributes to resistance of renal cancer cells to PI3K-mTOR inhibition - Earwaker, Philip; Anderson, Caroline; Willenbrock, Frances; Harris, Adrian L.; Protheroe, Andrew S.; Macaulay, Valentine M. (PloS one, 2018)
The outlook for patients with advanced renal cell cancer (RCC) has been improved by targeted agents including inhibitors of the PI3 kinase (PI3K)-AKT-mTOR axis, although treatment resistance is a major problem. Here, we aimed to understand how RCC cells acquire resistance to PI3K-mTOR inhibition. We used the RCC4 cell line to generate a model of in vitro resistance by continuous culture in PI3K-mTOR kinase inhibitor NVP-BEZ235 (BEZ235, Dactolisib). Resistant cells were cross-resistant to mTOR inhibitor AZD2014. Sensitivity was regained after 4 months drug withdrawal, and resistance was partially suppressed by HDAC inhibition, supporting an epigenetic mechanism. BEZ235-resistant cells up-regulated and/or activated numerous proteins including MET, ABL, Notch, IGF-1R, INSR and MEK/ERK. However, resistance was not reversed by inhibiting or depleting these pathways, suggesting that many induced changes were passengers not drivers of resistance. BEZ235 blocked phosphorylation of mTOR targets S6 and 4E-BP1 in parental cells, but 4E-BP1 remained phosphorylated in resistant cells, suggesting BEZ235-refractory mTORC1 activity. Consistent with this, resistant cells over-expressed mTORC1 component RAPTOR at the mRNA and protein level. Furthermore, BEZ235 resistance was suppressed by RAPTOR depletion, or allosteric mTORC1 inhibitor rapamycin. These data reveal that RAPTOR up-regulation contributes to PI3K-mTOR inhibitor resistance, and suggest that RAPTOR expression should be included in the pharmacodynamic assessment of mTOR kinase inhibitor trials.